Peripheries at the Centre : Borderland Schooling in Interwar Europe - Venken, Machteld 1980- (Contemporary European History, 2021)
"Following the Treaty of Versailles, European nation-states were faced with the challenge of instilling national loyalty in their new borderlands, in which fellow citizens often differed dramatically from one another along religious, linguistic, cultural, or ethnic lines. Peripheries at the Centre compares the experiences of schooling in Upper Silesia in Poland and Eupen, Sankt Vith, and Malmedy in Belgium - border regions detached from the German Empire after the First World War. It demonstrates how newly configured countries envisioned borderland schools and language learning as tools for realizing the imagined peaceful Europe that underscored the political geography of the interwar period"--